2021
DOI: 10.1186/s40364-021-00286-9
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological roles of myristoylated alanine-rich C-kinase substrate (MARCKS) in hematological malignancies

Abstract: The myristoylated alanine-rich C-kinase substrate (MARCKS) protein has been at the crossroads of multiple signaling pathways that govern several critical operations in normal and malignant cellular physiology. Functioning as a target of protein kinase C, MARCKS shuttles between the phosphorylated cytosolic form and the unphosphorylated plasma membrane-bound states whilst regulating several molecular partners including, but not limited to calmodulin, actin, phosphatidylinositol-4,5-bisphosphate, and phosphoinos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 167 publications
2
15
0
Order By: Relevance
“…Phosphorylation of MARCKS may in turn affect actin polymerization and cytoskeleton rearrangement affecting neuronal migration (Figure 4C). [ 73 ] Future studies may determine D‐cysteine binding regions in MARCKS to clarify the structural significance of this interaction due to the importance of MARCKS in regenerative medicine. [ 30 ]…”
Section: Marcks Is An Endogenous D‐cysteine Binding Proteinmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of MARCKS may in turn affect actin polymerization and cytoskeleton rearrangement affecting neuronal migration (Figure 4C). [ 73 ] Future studies may determine D‐cysteine binding regions in MARCKS to clarify the structural significance of this interaction due to the importance of MARCKS in regenerative medicine. [ 30 ]…”
Section: Marcks Is An Endogenous D‐cysteine Binding Proteinmentioning
confidence: 99%
“…Phosphorylated FoxO (inactive) translocates to the cytoplasm bound to 14-3-3. [72,73] Phosphorylation of MARCKS by PKC leads to inhibition of AKT activation. [74] Other targets of AKT include GSK3b, S6K, 4E-BP1 and caspase.…”
Section: In Vivo and In Vitro Studies With Exogenous D-cysteinementioning
confidence: 99%
“…As we did not describe it previously, this time we focused in detail on the physiological and pathological roles of this protein. MARCKS is the main target of protein kinase C. In the unphosphorylated form, it is bound to the plasma membrane, and after phosphorylation shuttling to the cytoplasm, it regulates different cellular processes, such as cytoskeletal reorganization, membrane trafficking, cell secretion, inflammatory response, cell migration, and mitosis [ 103 , 104 ]. It has been reported that MARCKS is associated with the development and progression of hematological cancers [ 103 ].…”
Section: Discussionmentioning
confidence: 99%
“…MARCKS is the main target of protein kinase C. In the unphosphorylated form, it is bound to the plasma membrane, and after phosphorylation shuttling to the cytoplasm, it regulates different cellular processes, such as cytoskeletal reorganization, membrane trafficking, cell secretion, inflammatory response, cell migration, and mitosis [ 103 , 104 ]. It has been reported that MARCKS is associated with the development and progression of hematological cancers [ 103 ]. The role of MARCKS in tumorigenesis, metastasis, and resistance to anti-cancer therapies of other cancers has also been described [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, MARCKS is involved in the regulation of a variety of cellular processes such as cytoskeletal reorganization, mitosis, adhesion, migration, vesicle trafficking, secretion, and signal transduction [ 10 ]. Accordingly, disturbances in MARCKS level or function are associated with numerous pathophysiological conditions [ 11 ], e.g., pulmonary [ 12 ] or neuronal diseases [ 13 ], cancer and metastasis [ 1 , 14 ], or fibrosis [ 15 ].…”
Section: Introductionmentioning
confidence: 99%